Antimicrobial resistance and its relationship with antimicrobial use on Austrian dairy farms - Werner, Thomas; Käsbohrer, Annemarie; Wasner, Barbara; Köberl-Jelovcan, Sandra; Vetter, Sebastian G.; Egger-Danner, Christa; Fuchs, Klemens; Obritzhauser, Walter; Firth, Clair L. (Frontiers in Veterinary Science, 2023)
The aim of this study was to investigate the prevalence of ESBL/AmpC-producing E. coli and the resistance pattern of commensal E. coli, as well as the link between the use of antibiotics (AMU) and the occurrence of resistance in E. coli on Austrian dairy farms. AMU data from 51 farms were collected over a one-year period in 2020. Faecal samples were collected from cows, pre-weaned and weaned calves in 2020 and 2022. Samples were then analysed using non-selective and selective agar plates, E. coli isolates were confirmed by MALDI-TOF analysis. Broth microdilution was used for antimicrobial susceptibility testing. The AMU of each farm was quantified as the number of Defined Daily Doses (nDDDvet) and Defined Course Doses (nDCDvet) per cow and year. Cephalosporins (mean 1.049; median 0.732 DDDvet/cow/year) and penicillins (mean 0.667; median 0.383 DDDvet/cow/year) were the most frequently used antibiotics on these farms, followed by tetracyclines (mean 0.275; median 0.084 DDDvet/cow/year). In 2020, 26.8% of the E. coli isolated were resistant to at least one antibiotic class and 17.7% of the isolates were classified as multidrug resistant (≥3 antibiotic classes). Out of 198 E. coli isolates, 7.6% were identified as extended-spectrum/AmpC beta-lactamase (ESBL/AmpC) producing E. coli. In 2022, 33.7% of E. coli isolates showed resistance to at least one antibiotic and 20.0% of isolates displayed multidrug resistance. Furthermore, 29.5% of the samples carried ESBL/AmpC-producing E. coli. In 2020 and 2022, the most frequently determined antibiotic resistances among commensal E. coli isolates were to tetracyclines, sulfonamides and penicillins. In addition, pre-weaned calves had the highest resistance rates in both years. Statistical analyses showed a significant association between low and high use AMU classifications for penicillins (in nDDDvet/cow/year) and their respective resistance among commensal E. coli isolates in 2020 (p=0.044), as well as for sulfonamide/trimethoprim (p=0.010) and tetracyclines (p=0.042). A trend was also noted between the total amount of antibiotics used on farm in 2020 (by nDDDvet/cow/year) and multidrug resistances in commensal E. coli isolated on farm that year (p=0.067). In conclusion, the relationship between AMU and antimicrobial resistance (AMR) on dairy farms continues to be complex and difficult to quantify.